From Private to Public: Narratives of Gender-Based Violence Among the Everyday Voices of the #MeToo Movement - Gjika, Anna (Journal of interpersonal violence, 2026)
In 2017, the #MeToo movement garnered international attention when millions of people used the hashtag to share personal experiences of sexual violence. The present study examines how noncelebrity users discussed their experiences of sexual victimization through a qualitative and quantitative content analysis of a random sample of #MeToo tweets (N = 1,427). We found that survivors prioritized details about the “who,” “what,” “where,” “when,” “why,” and “how” of trauma in their disclosures. Key themes in their responses included child sexual abuse (22.7%), long-term adverse effects (17.6%), and polyvictimization (10.4%) across the life course. Survivors also utilized #MeToo to highlight the prevalence of violence against women (26.4%) and offer critiques of rape culture and social structures (23.9%) as indirect causes of their victimization and subsequent negative experiences. Our analysis demonstrates the utility of Twitter for broadening current understandings of the context in which sexual violence occurs, while also offering a nuanced analysis of the persisting difficulties many survivors face in narrating personal experiences of violence.